Hydrograph Shape Impact on Sand Infiltration and Sediment Transport Dynamics in Gravel‐Bed Rivers. Issue 10 (29th September 2022) - Ravazzolo, D.; Mao, L.; Friedrich, H.
Abstract: Sand (i.e., < 2 mm) infiltration into a gravel bed is recognized to affect sediment dynamics of coarser fractions (i.e., entrainment and transport rate), near‐bed velocities, bed morphology, and to pose significant engineering and ecological issues. Local hydraulics, sediment dynamics, and sand infiltration into the gravel matrix are related and mutually affect each other in gravel‐bed rivers. However, relatively little research has been done to explore sediment dynamics and sand infiltration in a mobile gravel‐bed under unsteady flow conditions. In the present study, we experimentally simulated three hydrographs of different durations of rising and falling limbs, and monitored sand infiltration over beds with a coarse and a fine grain size distribution. Results confirmed that the addition of sand enhances sediment dynamics. Moreover, the shape of the rising limb of the hydrograph was responsible for altering identified sand infiltration processes and bedload rate. Short time‐to‐peak floods (i.e., short time from the start to the peak of the hydrograph) experienced higher sediment transport rates during the falling limb than the rising limb of the hydrograph, favoring sand infiltration. In contrast, long time‐to‐peak floods (i.e., long time from the start to the peak of the hydrograph) experienced higher sediment transport rates during the rising limb than the falling limb of the hydrograph, resulting in reduced sand infiltration. Plain Language Summary: Understanding how sediment is transported during floods is important, as their movement affects channel morphology and river ecology. Fine sediment can infiltrate gravel bed‐rivers, a process that depends on the local hydraulics, the size of the fine sediment and the movement of the coarser sediment in the channel bed. Very little research has been done to explore sediment dynamics and sand infiltration in a mobile gravel‐bed under unsteady flow conditions. In this work, we experimentally simulated three hydrographs of different durations of rising and falling limbs, and monitored sand infiltration over beds with coarse and fine grain size distributions. Results indicate that the addition of sand enhances the bed's dynamics. For long time‐to‐peak hydrographs, we observed larger and smoother sediment transport rates during the rising limb, compared to the falling limb, with the differences attributable to the interaction between sand and sediment. Sand covered the sediment bed for longer periods at lower flow rates during long time‐to‐peak hydrographs, compared to short time‐to‐peak hydrographs. In addition, lower sand infiltration rates were observed for the rising limb of long time‐to‐peak hydrographs. Key Points: Sand addition enhances sediment dynamics (i.e., entrainment and transport rate) The shape of the rising limb of the hydrograph alters sediment transport and sand infiltration Increased bed porosity and reduced sand infiltration were observed for the rising limb of long time‐to‐peak flood hydrographs